2020
DOI: 10.1002/hbm.24931
|View full text |Cite
|
Sign up to set email alerts
|

Temporal cues trick the visual and auditory cortices mimicking spatial cues in blind individuals

Abstract: In the absence of vision, spatial representation may be altered. When asked to compare the relative distances between three sounds (i.e., auditory spatial bisection task), blind individuals demonstrate significant deficits and do not show an event-related potential response mimicking the visual C1 reported in sighted people. However, we have recently demonstrated that the spatial deficit disappears if coherent time and space cues are presented to blind people, suggesting that they may use time information to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 61 publications
5
22
0
Order By: Relevance
“…We wished to test if, with increasing BD, temporal cues during a spatial bisection task alter performance and recruitment of the visual and auditory cortices of LB individuals in a manner similar to that seen in early blind individuals (Gori et al, 2020b). In fact, we previously showed that in early blind people the second sound (S2) of the spatial bisection does not produce the early contralateral occipital activation observed in sighted individuals (Campus et al, 2019).…”
Section: Behavioral and Eeg Data Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…We wished to test if, with increasing BD, temporal cues during a spatial bisection task alter performance and recruitment of the visual and auditory cortices of LB individuals in a manner similar to that seen in early blind individuals (Gori et al, 2020b). In fact, we previously showed that in early blind people the second sound (S2) of the spatial bisection does not produce the early contralateral occipital activation observed in sighted individuals (Campus et al, 2019).…”
Section: Behavioral and Eeg Data Analysismentioning
confidence: 99%
“…The time employed to answer was recorded to ensure participants were engaged in the task. For more information about setup and procedure refer to Gori et al (2020b).…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations